2013
DOI: 10.1097/brs.0b013e3182715bc3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Surgical Outcome in Cervical Spondylotic Myelopathy

Abstract: Age and baseline mJOA scores were highly predictive of outcome for patients undergoing surgical treatment of CSM. The degree of spinal cord compression and patterns of signal intensity changes on T1/T2 weighted images were not independently predictive of outcome, but it was found to correlate with the functional status at the time of presentation and age of the patient. The duration of symptoms correlated well with preoperative functional status but did not seem to affect the postoperative outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
75
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 25 publications
9
75
1
Order By: Relevance
“…The Japanese Orthopaedic Association motor scoring system has been used previously for children with cervical spine instability 9,18 . Additionally, in some but not all studies of patients with degenerative cervical spine disease, the Japanese Orthopaedic Association motor scoring system has been a predictor of outcome of decompressive surgery for cervical spondylolytic myelopathy 19,20 and has also shown a correlation with preoperative central motor conduction time as measured with transcranial magnetic stimulation 21 . Although some of the questions are clearly related to Japanese culture, we believe that the scoring system contains useful data on cervical spinal cord deficits in children with various cultural backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…The Japanese Orthopaedic Association motor scoring system has been used previously for children with cervical spine instability 9,18 . Additionally, in some but not all studies of patients with degenerative cervical spine disease, the Japanese Orthopaedic Association motor scoring system has been a predictor of outcome of decompressive surgery for cervical spondylolytic myelopathy 19,20 and has also shown a correlation with preoperative central motor conduction time as measured with transcranial magnetic stimulation 21 . Although some of the questions are clearly related to Japanese culture, we believe that the scoring system contains useful data on cervical spinal cord deficits in children with various cultural backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…This time frame implicates inherent regenerative or plastic changes within the spinal cord. Nevertheless, many patients remain disabled [29], and there are nonsurgical treatments available for improving outcome for CSM.…”
Section: Introductionmentioning
confidence: 99%
“…The mJOA score has been shown to be a predictor of outcomes after decompressive surgery for CSM. 33 In one study, severe myelopathy (JOA <7) was associated with a good outcome in 55% of patients versus 70% in patients with mild disease. 34 Others have reported that CMCT correlates with mJOA at both preoperative and postoperative time points in patients with severe CSM 1,2,12 .…”
Section: Discussionmentioning
confidence: 96%